What have we learned from two-pore potassium channels? : their molecular configuration and function in the human heart - Szűts, Viktória (Acta Biologica Szegediensis, 2012)
Two-pore domain potassium channels (K2P) control excitability, stabilize the resting membrane potential below firing threshold, and accelerate repolarisation in different cells. Until now, fifteen different genes for the six K2P channel subfamily were cloned. The pore-forming part is translated from two genes and they are built up from a dimer of two two-unit transmembrane domains functioning with a wide spectrum of physiological profiles. K2P ion channels were discovered in the last two decades and gave novel opportunity to recognize the complex molecular mechanism of the potassium ion flux, and may lead to the design of individual drug targeting in the future. In this review, we summarise the structure, function, channelopathies and pharmacological silhouette of the two-pore potassium channels in the human tissues. In addition, we present the computer model of the partially reconstructed wild type K2P1/TWIK1 lacking the intracellular C and N terminal loops.